Shadow Exchange Rate Effectiveness in Stock Market Performance Indicators - Ameer Ali Khaleel, (Technium Business and Management, 2024)
The objective of this study is to quantify the difference between the official and unofficial exchange rates of the dollar (shadow) and subsequently assess the degree to which this difference affects the performance of the Iraqi stock market. The official exchange rate installed in the Central Bank of Iraq's window for selling foreign currency and the exchange rate announced on social media platforms such as Facebook or the Al-Kifah Stock Exchange—which represents the months at the level of Iraq from January 1, 2019 to December 31, 2023—were the basis for measuring the gap. It amounts to 60 views per month. The research assumed one main hypothesis: there is no statistically significant effect of the dollar exchange rate gap on the trading indicators of the Iraq Stock Exchange. The most prominent conclusion was that the ISX60 index is affected by fluctuations in unofficial exchange rates. were to emphasize the need to put reforms in the foreign trade system by zeroing in on the problems of tax trusts and customs clearance.